Financial Performance : The Effect of Green Accounting on Firm Value - Okta Amiko Naka; Rina Yuniarti; Hernadianto Hernadianto; Yusmaniarti Yusmaniarti; Marini Marini (International Journal Business, Management and Innovation Review, 2025)
Technological advances, changing consumer patterns, and the need for the economy are expected to drive large companies in the future of the business world. The purpose of this study was to examine Green Accounting on firm value mediated by financial performance.  The population in this study were manufacturing companies with purposive sampling technique. The data analysis technique used is SEM PLS processed with WarpPLS 7.0. The results showed that Green Accounting has a significant positive effect on firm value. This shows that the findings of this study indicate that Green Accounting can increase firm value. Financial performance is able to mediate the effect of Green Accounting on firm value. Increased investor and public confidence encourages companies to disclose environmental reports in a transparent and accountable manner.